Testing the demographic effects of divergent immigrants on small populations of Trinidadian guppies. (14th June 2016) - Kronenberger, J. A.; Funk, W. C.; Smith, J. W.; Fitzpatrick, S. W.; Angeloni, L. M.; Broder, E. D.; Ruell, E. W.
Abstract: Augmenting small and isolated populations with immigrants from elsewhere is a potentially powerful, yet controversial management tool. The goal of this approach was to increase population sizes via demographic and/or genetic rescue, but augmentation can also have the unintended consequence of breaking down local adaptation and reducing population fitness through outbreeding depression. In theory, outbreeding depression is more likely the more divergent immigrants are from the recipient population. Managers should therefore choose immigrant populations that are as adaptively and genetically similar as possible. However, for species of conservation concern, divergent source populations are often the only option. A crucial question that remains in applied conservation is whether the positive effects of augmentation with divergent immigrants will outweigh the potential risks of outbreeding depression. Here, we evaluate the demographic effects of augmenting small, inbred laboratory populations of Trinidadian guppies with two different types of immigrants: (1) adaptively divergent but genetically similar or (2) adaptively similar but genetically divergent, and compare them against the demography of control populations with no immigration. After 1–2 generations, we found that adult abundance remained constant or slightly declined over the duration of the experiment in the control populations. In contrast, adult recruitment and total abundance increased in augmented populations. Furthermore, treatments that received immigrants from the adaptively similar but genetically divergent population attained overall larger population sizes than those that received immigrants from the adaptively divergent but genetically similar population. Although our experimental design could not parse out the effects of demographic and genetic rescue, our results do suggest that augmentation can be better than no action, even in situations where only divergent immigrant sources are available. Abstract : Augmenting threatened populations with individuals from elsewhere is a contentious conservation strategy, in part because immigrants can diminish overall fitness of the target population. This risk is further elevated if immigrants are divergent from recipients. In this study, we demonstrate via a controlled laboratory experiment with Trinidadian guppies that divergent immigrants can have positive demographic effects on small populations.